Pemohon Tanggung Jawab Negara Dalam Hukum Internasional (Studi Kritis Terhadap ILC Draft On State Responsibility 2001) - sefriani sefriani (Jurnal Hukum IUS QUIA IUSTUM, 2005)
Up to the present, Ahe discussion of secondary rules or state responsibility law under International law is still on the debate of the international community. However, state responsibility can be claimed on the international relations when a state is disadvantaged by the other state, because of the violation of the obligations which raises from treaty, customary international law, or because of not fulfilled the international court decision.